e-Info_JK formation committee system for the School of Civil Engineering (PKA) Universiti Teknologi MARA / Azlinda Saadon ... [et al.] - Saadon, Azlinda; Kamaruding, Musmuliadi; Mohd Dzulkifli, Syahrun Neizam; Mukri, Mazidah; Mohd Saim, Noraida; Khairuddin, Dzulaikha; Abdull Rahman, Siti Hamidah (2021)
The formation of committee in an organization is very important in driving the success of achieving the mission and vision of the organization. The committees established with specific functions and composed of staff at various levels can together move the organization unit to achieve the work targets set. Conventional method involved tedious manual appointment of academic staff including the preparation of appointment letter and workload calculation. This conventional method takes a long time, unsystematic management and updating of records made it difficult for information to be accessed in the required time. In addition, it is quite challenging to ensure equal distribution of workload to be made among the organization members. For an organization with large number of staff including academic, technical, administrative, and management staff, for instance, the School of Civil Engineering (PKA) under the College of Engineering, Universiti Teknologi MARA (UiTM), several constraints will be raised in the work process of appointment of committee members and the formation of committees. To overcome the problem, this innovation highlights the digital system of the Formation and Monitoring Committee, known as e-Info_JK under the Quality Assurance Unit, School of Civil Engineering, Universiti Teknologi MARA (UiTM) Shah Alam. This e-Info_JK system is also integrated with the website of the Quality Assurance Unit and will enhance the development of formation and Monitoring Committee including the calculation of workload, formulation template, pivot chart for the division of committee appointment, and appointment letter retrieval. The e-Info_JK system require less time and able to minimize calculation error by establishing a score reference value to facilitate the division of the committee and ensure fair and equitable distribution among faculty members.